Analysis of Farmers' Group Capabilities in the City of Sawahlunto - Dedi Kusmiadi; Hery Bachrizal Tanjung; Sri Wahyuni (International Journal of Social Service and Research, 2023)
Agriculture plays an important role in the Indonesian economy, especially in rural areas which are dominated by farmers whose income is from agricultural products. Increasing farmer welfare is the key to agricultural development. This can be achieved through increasing agricultural productivity, access to efficient markets, and developing human resources and farmer institutions. Farmer groups are a key element in agricultural development, enabling the exchange of information, training and collaboration between farmers. Farmer Group capability class assessment is an important tool in understanding the dynamics and development of this group. In Sawahlunto City, the majority of Farmer Groups are still in the beginner and advanced classes, with only a few reaching the intermediate class. Many factors influence the ability of Farmer Groups, including changes in conditions in the field, structural changes, and the formation of groups just to get government assistance. Therefore, assessing the ability class of Farmer Groups must be the basis for coaching and empowering this group, so that it can play a more effective role in agricultural development.